Interaction of highly nonlinear solitary waves with rigid polyurethane foams. (November 2018) - Schiffer, Andreas; Lee, Dongwon; Kim, Eunho; Kim, Tae-Yeon
Highlights: Interaction of solitary waves with rigid PU foam are numerically/experimentally investigated. Coupled discrete/finite element method is efficient for simulating the chain-foam interactions. Reflected solitary waves are sensitive to the elasto-plastic behaviour of PU foam. Time delay and amplitude of the reflected solitary wave contain important information of elasto-plastic properties. A granular sensor based on solitary wave shows great potential to evaluate the mechanical properties of PU foam. Abstract: Experiments and simulations are performed to study the interaction of solitary waves in a granular crystal with a plastically compressible and rate-sensitive test medium in the form of rigid polyurethane (PU) foam. We study the effects of the foam's compressive strength and elastic modulus on the nonlinear wave dynamics near the interface and on the formation of reflected solitary waves. Experiments are conducted using a granular crystal composed of a vertical array of spherical steel particles, directly contacting the foamed polyurethane samples. Single solitary waves are generated in the chain through striker particle impact, and the temporal profiles of the incident and reflected solitary waves are recorded by placing an instrumented sensor particle in the chain. The measurements show that travel time and wave amplitude of the reflected solitary waves are highly sensitive to the elasto-plastic properties of the inspection medium, particularly when the intensity of the incident solitary waves is increased. The measurements were compared to the predictions obtained with a coupled discrete/finite element model and good agreement was reported. The predictions show that when the amplitude of the incident solitary wave increases, the response transitions from an elastic regime to a regime dominated by plastic compression.